2014
DOI: 10.1093/nar/gku768
|View full text |Cite
|
Sign up to set email alerts
|

Translational stalling at polyproline stretches is modulated by the sequence context upstream of the stall site

Abstract: The polymerization of amino acids into proteins occurs on ribosomes, with the rate influenced by the amino acids being polymerized. The imino acid proline is a poor donor and acceptor for peptide-bond formation, such that translational stalling occurs when three or more consecutive prolines (PPP) are encountered by the ribosome. In bacteria, stalling at PPP motifs is rescued by the elongation factor P (EF-P). Using SILAC mass spectrometry of Escherichia coli strains, we identified a subset of PPP-containing pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
108
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 97 publications
(114 citation statements)
references
References 37 publications
6
108
0
Order By: Relevance
“…As a further refinement of our analysis of pausing at PP(X) motifs, we found that the residue just upstream, Z in ZPP(X), has a small effect on the average pause score (Figure 3B). In general, motifs associated with high pausing scores have Lys, Glu, Ile, Val, His, Arg, and Pro at the Z (−3) position and were observed to reduce lacZ expression in a reporter system (Starosta et al, 2014a). We note that the presence of Arg at the −3 position enhances stalling in the RXP(P) motif characterized in our previous study (Woolstenhulme et al, 2013) and at the RPPP pause in recG in Figure 2A.…”
Section: Resultsmentioning
confidence: 99%
“…As a further refinement of our analysis of pausing at PP(X) motifs, we found that the residue just upstream, Z in ZPP(X), has a small effect on the average pause score (Figure 3B). In general, motifs associated with high pausing scores have Lys, Glu, Ile, Val, His, Arg, and Pro at the Z (−3) position and were observed to reduce lacZ expression in a reporter system (Starosta et al, 2014a). We note that the presence of Arg at the −3 position enhances stalling in the RXP(P) motif characterized in our previous study (Woolstenhulme et al, 2013) and at the RPPP pause in recG in Figure 2A.…”
Section: Resultsmentioning
confidence: 99%
“…3B) is reminiscent of proline motifs that are poorly translated even by the drug-free ribosomes (22,23). Like with macrolide-dependent arrest, ribosome stalling at the proline motifs is influenced by the nascent chain residues proximal to the C terminus (24,25). On the other hand, some other short motifs, which are known to stall drug-free ribosomes (26), were not enriched in the sites of macrolide-dependent stalling.…”
Section: Discussionmentioning
confidence: 99%
“…Binding of HygA, A201A and erythromycin (ERY) to an empty E. coli ribosome was monitored using a competition assay with radiolabelled [ 14 C]-erythromycin (170 dpm/pmol) as described before (Karahalios et al, 2006; Petropoulos et al, 2009; Starosta et al, 2010). The position of the ribosome on the mRNA was monitored using a toe-printing assay based on the in vitro coupled transcription-translation system using the PURExpress Δaa ΔtRNA kit (New England Biolabs) as described previously (Starosta et al, 2014). Further details on the in vitro translation and binding assays are provided in the Supplemental Experimental Procedures…”
Section: Methodsmentioning
confidence: 99%